Intercultural Communicative Competence in the Interpreting Classroom: Evidence from Japanese–English into Indonesian Consecutive Interpreting Practice - Susi Septaviana Rakhmawati; Dewi Kusrini (Datokarama English Education Journal, 2024)
Intercultural Communicative Competence (ICC) is increasingly recognized as a foundational skill for interpreter trainees, yet its systematic integration into interpreting pedagogy remains underexplored, particularly in the Indonesian higher education context. This study investigates how ICC, operationalized through Byram's (1997) five-savoir framework, manifests in consecutive interpreting performance and intercultural interaction among undergraduate students enrolled in English study programs at a public university in West Java, Indonesia. Drawing on two complementary datasets, (1) pre-test and post-test interpreting transcripts from 15 students interpreting authentic Japanese–English political speeches into Indonesian, and (2) post-conference questionnaire data and observation notes from an Online International Student Conference (OISC) involving 12 Indonesian and 15 Japanese undergraduates, the study employs thematic analysis to examine ICC development of attitudes, knowledge, and skills aspects. Findings indicate that structured interpreting instruction grounded in genre awareness and intercultural reflection produces measurable gains in accuracy, pragmatic equivalence, and cultural mediation strategies. Students who developed stronger ICC demonstrated greater tolerance for ambiguity, more sophisticated discourse repair, and heightened awareness of ideological dimensions in source texts. The study proposes an ICC-informed model for interpreting pedagogy in Indonesian English study programs and identifies implications for curriculum design, assessment rubric development, and international collaboration.